Mapping the association between mental health and people's perceived and actual ability to practice hygiene-related behaviours in humanitarian and pandemic crises: A scoping review. - Emily Yasmin Ghassemi; Astrid Hasund Thorseth; Karine Le Roch; Thomas Heath; Sian White (PLoS ONE)
Humanitarian crises such as disease outbreaks, conflict and displacement and natural disasters affect millions of people primarily in low- and middle-income countries. Here, they often reside in areas with poor environmental health conditions leading to an increased burden of infectious diseases such as gastrointestinal and respiratory infections. Water, sanitation, and hygiene behaviours are critical to prevent such infections and deaths. A scoping review was conducted to map out what is known about the association between three mental health disorders and people's perceived and actual ability to practice hygiene-related behaviours, particularly handwashing, in humanitarian and pandemic crises. Published and grey literature was identified through database searches, humanitarian-relevant portals, and consultations with key stakeholders in the humanitarian sector. 25 publications were included, 21 were peer-reviewed published articles and four were grey literature publications. Most of the studies were conducted in mainland China (n = 12) and most were conducted in an outbreak setting (n = 20). Six studies found a positive correlation between handwashing and anxiety where participants with higher rates of anxiety were more likely to practice handwashing with soap. Four studies found an inverse relationship where those with higher rates of anxiety were less likely to wash their hands with soap. The review found mixed results for the association between handwashing and depression, with four of the seven studies reporting those with higher rates of depression were less likely to wash their hands, while the remaining studies found that higher depression scores resulted in more handwashing. Mixed results were also found between post-traumatic stress disorder (PTSD) and handwashing. Two studies found that lower scores of PTSD were associated with better hygiene practices, including handwashing with soap. The contradictory patterns suggest that researchers and practitioners need to explore this association further, in a wider range of crises, and need to standardize tools to do so.